Revision of the Metallactus minax Suffrian, 1866 species-group (Coleoptera: Chrysomelidae: Cryptocephalinae) - Sassi, Davide (Zootaxa, 2025)
Three species of Metallactus Suffrian, 1866 have been revised, redescribed and critically discussed. One additional species, formerly included in Griburius Haldeman, 1849 has been transferred to Metallactus: Metallactus abstersus (Suffrian, 1866) comb. nov. The following synonymies are proposed: Metallactus minax Suffrian, 1866 = Metallactus mosei Schöller, 2003 syn. nov. Metallactus abstersus (Suffrian, 1866) = Metallactus incultus Suffrian, 1866 syn. nov. Type series were tracked down and a lectotype was designated for Metallactus minax, Metallactus abstersus and Metallactus incultus. Illustrations and current known distribution of the treated species are given. M. minax, formerly known from Brazil only, is reported as new for Argentina and Paraguay. Additionally, Metallactus tommasoi sp. nov. from Brazil is described as new to science.